2023
DOI: 10.1177/00420980221148388
|View full text |Cite
|
Sign up to set email alerts
|

Progressive cities: Urban–rural polarisation of social values and economic development around the world

Abstract: In contrast to the conservative values of rural populations, cities are often seen as bulwarks of more tolerant, liberal and progressive values. This urban–rural divide in values has become one of the major fault lines in Western democracies, underpinning major political events of the last decade, not least the election of Donald Trump. Yet, beyond a small number of countries, there is little evidence that cities really are more liberal than rural areas. Evolutionary modernisation theory suggests that socio-ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…We maintain that urbanization leads to the rise of contradictory forms of nationalism in cities: civic-liberal and ethnic-nativist, thereby affecting the strategies of nationalist parties' elites. On the one hand, it leads to more liberal and secular values due to better access to education, higher economic prospects, and exposure to diversity (Wilkinson 2019, andLuca et al 2023). On the other hand, it motivates nativist and nationalist attitudes toward immigrants and refugees due to economic competition, cultural differentiation, and political polarization.…”
Section: Nationalism and Attitudes Toward Immigrants And Refugeesmentioning
confidence: 99%
“…We maintain that urbanization leads to the rise of contradictory forms of nationalism in cities: civic-liberal and ethnic-nativist, thereby affecting the strategies of nationalist parties' elites. On the one hand, it leads to more liberal and secular values due to better access to education, higher economic prospects, and exposure to diversity (Wilkinson 2019, andLuca et al 2023). On the other hand, it motivates nativist and nationalist attitudes toward immigrants and refugees due to economic competition, cultural differentiation, and political polarization.…”
Section: Nationalism and Attitudes Toward Immigrants And Refugeesmentioning
confidence: 99%
“…Social and economic milieux and localized patterns of social interaction, institutions and rules, social identities, and cultural schemas shape the political preferences of the people who live there. Considerable recent research has shown that such place effects are an important component of contemporary urban-rural divides in the United States and elsewhere (Cantoni & Pons, 2022;Huijsmans et al, 2021;Luca et al, 2023;Martin & Webster, 2020). As Gimpel et al (2020) have argued:…”
Section: Places (Contextual Effects)mentioning
confidence: 99%
“…Hiner [21], as a synthesis of the above, considers that the rural-urban interface has two categories of elements, as follows: the first represents the place with all its characteristics, while the second is the social-political environment. In addition to these, the new cleavage that appeared between urban and rural, in relation to the tolerance towards the progressive values promoted by the city [22], calls for a permanent update of urban and regional development policies.…”
Section: Introductionmentioning
confidence: 99%